2020
DOI: 10.3389/fonc.2020.01104
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA DGKB Promotes the Progression of Neuroblastoma by Targeting miR-873/GLI1 Axis

Abstract: Accumulated evidences suggested that circular RNAs (circRNA) played critical roles in tumorigenesis and progression. To our knowledge, no study reported the function of circular RNA DGKB (circDGKB, circRNA ID: hsa_circ_0133622) on progression of neuroblastoma (NB). Here, we showed that circDGKB was upregulated in NB tissues compared to the normal dorsal root ganglia. Moreover, the expression level of circDGKB was negatively correlated with the survival rate of NB patients. Mechanically, overexpression of circD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…By detecting and comparing the expression of circDGKB in blood samples from neuroblastoma patients and healthy subjects, the expression level of circDGKB was significantly increased in neuroblastoma patients. 300 Furthermore, the level of circDGKB had an essential clinical value in diagnosing neuroblastoma with an area under the curve (AUC) of 0.7778. The results of the Kaplan–Meier analysis showed that patients with a high level of circDGKB had lower survival rates.…”
Section: Lncrnas and Circrnas In Neuroblastomamentioning
confidence: 99%
“…By detecting and comparing the expression of circDGKB in blood samples from neuroblastoma patients and healthy subjects, the expression level of circDGKB was significantly increased in neuroblastoma patients. 300 Furthermore, the level of circDGKB had an essential clinical value in diagnosing neuroblastoma with an area under the curve (AUC) of 0.7778. The results of the Kaplan–Meier analysis showed that patients with a high level of circDGKB had lower survival rates.…”
Section: Lncrnas and Circrnas In Neuroblastomamentioning
confidence: 99%
“…Circ-DGKB (hsa_circ_0133,622) expression was upregulated in NB tissues compared to normal dorsal root ganglia and negatively correlated with survival in NB patients. Circ-DGKB overexpression promoted NB cell proliferation, migration, invasion, and tumorigenesis and reduced apoptosis, promoting NB progression by targeting the miR-873/GLI1 axis in vitro and in vivo ( Yang et al, 2020 ). Circ-CUX1 and PHF20 are upregulated in NB tissues and cells, while miR-338-3p expression is significantly decreased.…”
Section: Roles and Significance Of Circrnas In Pediatric Malignant Solid Tumorsmentioning
confidence: 99%
“…The subject operating characteristic (ROC) curve was applied to investigate the diagnostic value of circ-HMGCS1 in distinguishing HB tissue from normative tissue showing that circ-HMGCS1 had diagnostic value (Area Under Curve (AUC) = 0.8283), with high expression of circ-HMGCS1 predicting poor prognosis in HB patients by Kaplan-Meier survival curve analysis ( Zhen et al, 2019 ). The expression of circ-DGKB in blood was found to be of clinical importance in the diagnosis of NB by ROC analysis (AUC = 0.7778), with Kaplan-Meier analysis showing that patients with high levels of circ-DGKB expression had a lower survival rate ( Yang et al, 2020 ). Zhang et al divided NB patients into high and low circ-CUX1 expression groups according to the median value of circ-CUX1 expression for survival analysis revealing that high expression of circ-CUX1 in NB patients was associated with shorter survival times.…”
Section: Roles and Significance Of Circrnas In Pediatric Malignant Solid Tumorsmentioning
confidence: 99%
“…Hsa_circ_0000069 can sponge miR-873-5p, which can promote the expression of TUSC3, thereby promoting the proliferation, migration, and invasion of CC cells ( 133 ). In Neuroblastoma, circDGKB can sponge miR-873-5p to increase the expression of ZEB1 and GLI1, and promote the occurrence and development of cancer ( 134 ). circ-UMAD1 can sponge miR-873-5p, thereby up-regulating the expression of Galectin-3 and inducing lymphatic metastasis of PTC ( 135 ).…”
Section: The Regulation Of Mir-873-5p In Human Cancermentioning
confidence: 99%